Biomechanics : trends in modeling and simulation - Holzapfel, Gerhard A.; Ogden, R. W., 1943- (Springer, 2017)
The book presents a state-of-the-art overview of biomechanical and mechanobiological modeling and simulation of soft biological tissues. Seven well-known scientists working in that particular field discuss topics such as biomolecules, networks and cells as well as failure, multi-scale, agent-based, bio-chemo-mechanical and finite element models appropriate for computational analysis. Applications include arteries, the heart, vascular stents and valve implants as well as adipose, brain, collagenous and engineered tissues. The mechanics of the whole cell and sub-cellular components as well as the extracellular matrix structure and mechanotransduction are described. In particular, the formation and remodeling of stress fibers, cytoskeletal contractility, cell adhesion and the mechanical regulation of fibroblast migration in healing myocardial infarcts are discussed. The essential ingredients of continuum mechanics are provided. Constitutive models of fiber-reinforced materials with an emphasis on arterial walls and the myocardium are discussed and the important influence of residual stresses on material response emphasized. The mechanics and function of the heart, the brain and adipose tissues are discussed as well. Particular attention is focused on microstructural and multi-scale modeling, finite element implementation and simulation of cells and tissues.
Keywords: Biomechanics.; elektronické knihy; electronic books